2012
DOI: 10.1080/03067319.2010.534159
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic photochemistry of diclofenac in the presence of natural dissolved organic chromophoric material and nitrate

Abstract: Photolysis experiments with diclofenac (DCF) in aqueous solutions under different artificial irradiations were performed to characterise the influence of natural chromophoric dissolved organic material (CDOM) and nitrate ions (NO À 3 ) on the transformation rate of DCF. The irradiations were carried out by a low-energy UVA-vis (315-400-800 nm) and powerful UVB-uva (280-315-400 nm) lights simulating natural conditions. Alterations of molecular size distributions and optical properties of CDOM after different ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A greater intensity light source will produce a larger direct photolysis rate constant, and thus a shorter half-life. 61,102 If these experiments are done under natural sunlight, a sufficient approximation can generally be obtained regarding the contribution of direct photolysis towards limiting the persistence of that compound in a real system. Because most sunlight photolysis experiments are done in small isolated vessels, it is generally assumed only to approximate near-surface processes, as light attenuation becomes signicant with increasing depth.…”
Section: Direct Photolysis Quantum Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater intensity light source will produce a larger direct photolysis rate constant, and thus a shorter half-life. 61,102 If these experiments are done under natural sunlight, a sufficient approximation can generally be obtained regarding the contribution of direct photolysis towards limiting the persistence of that compound in a real system. Because most sunlight photolysis experiments are done in small isolated vessels, it is generally assumed only to approximate near-surface processes, as light attenuation becomes signicant with increasing depth.…”
Section: Direct Photolysis Quantum Yieldsmentioning
confidence: 99%
“…However, the value of Andreozzi et al 41 is approximately two orders of magnitude smaller ( Table 2 also point to characterization of light intensity as a potential factor leading to major uncertainties in quantum yield determination. Peuravuori 102 found that the quantum yield for diclofenac determined using a full spectrum sunlight simulator was three orders of magnitude smaller than with the low pressure mercury lamp (280-400 nm), 102 pointing to the incident light measurement as a major source of uncertainty. However, other aspects of this study raise concern regarding the validity of the experimental data.…”
Section: View Article Onlinementioning
confidence: 99%
“…Several reports detail how the medium influences DCF photoconversion reactions catalyzed and uncatalyzed. Physical and chemical factors, as well as the medium matrix and other solution components, were shown to have an impact on the photoconversion rate [ [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. As a result, there is a significant need for systematic qualitative and quantitative analyses of such effects.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have described experimentally the effects of the medium on DCF photoconversion reactions through catalyzed and uncatalyzed processes, where the photoconversion rate was affected by the medium matrix and other physicochemical parameters of the medium. [24][25][26][27][28][29][30] Importantly, however, the quantification and rationalization of the influence of various medium parameters are of great significance toward gaining insights into the effects of medium on the mechanistic patterns of such photoconversion reactions; this includes not only the solvent's polarity, but also other important parameters such as specific solvent/ solute interactions.…”
Section: Introductionmentioning
confidence: 99%